DEVELOPING HOT POTATOES-BASED MATERIALS FOR ENGLISH TEACHING AND LEARNING AT SMK - Safer, Fran; Salam, Urai; ., Ikhsanudin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: The aim of this study was to develop mulimedia-based materials for teaching and learning English at SMK Negeri 1 Balai. The development of Hot potatoes-based materials adopted research and development study. This study applied ADDIE steps as follows. Firstly, need analysis. The need analysis found that there was a need of multimedia-based materials for teaching and leaning English at SMK Negeri 1 Balai. Secondly, design, the design of the materials was based on need analysis and english subject curriculum. The blue print or lay out of the materials were created in this stage. Thirdly, development. The development involves some author wares, such as hot potatoes application,adobe reader, picture editors and web page maker. The pilot product was created in this stage. fourthly was implementation of the materials. There were 30 students of SMK Negeri 1 Balai were involved in this stage. Based on thier responses, there is norevision on the materials. The last step was evaluation. This stage involved two media-materials experts and a language expert. They evaluated and responded that the materials are useable for teaching and learning English. Keywords: ADDIE steps, Multimedia-based materials Abstrak: Penelitian ini dilakukan dengan tujuan untuk mengembangkan bahan ajar berbasis multimedia untuk pembelajaran bahasa Inggris di SMK Negeri 1 Balai. Pengembangan bahan ajar ini menggunakan metode penelitian riset dan pengembangan. Penelitian ini menggunakan langkah-langkah ADDIE. Langkah pertama yaitu analisis kebutuhan. Pada tahap ini ditemukan bahwa adanya kebutuhan akan bahan ajar berbasiskan multimedia untuk proses pembelajaran pada SMK Negeri 1 Balai. Tahap kedua, Desain bahan ajar ini berdasarkan pada hasil dari analisis kebutuhan dan kurikulum bahasa inggris. layout dari bahan ajar dibuat pada tahap ini. Tahap ketiga yaitu pengembangan. Tahap ini menggunakan beberapa software pendukung, seperti aplikasi hot potatoes, picture editors, dan web page maker. Tahap ini menghasilkan bahan ajar percobaan. Tahap keempat adalah implementasi dari bahan ajar. Tahap ini melibatkan 30 orang siswa SMK Negeri 1 Balai. Berdasarkan respons mereka, bahan ajar ini tidak membutuhkan revisi. Langkah terakhir adalah evaluasi. Tahap ini melibatkan dua ahli bahan ajar multimedia dan seorang ahli bahasa. Mereka mengevaluasi dan merespon bahwa bahan ajar ini dapat digunakan didalam proses pembelajaran. Kata kunci: langkah-langkah ADDIE, Bahan ajar berbasis multimedia